Combined effects of physical activity and life events on depression and PTSD in Chinese students aged 16–24 years - Wang, Zhifeng; Wang, Fengyun; Jiang, Bing; Xue, Haihong; Zhao, Ming; Wang, Dongmei (Frontiers in Public Health, 2024)
Background Life events are important risk factors for depression and post-traumatic stress disorder (PTSD). Physical activity is a beneficial behavior to physiological and psychological health. While it has not been reported at present the combined effect of physical activity and life events on individual depression and PTSD, and whether it can alleviate the psychological risks induced by life events. Objective To comprehensively investigate the current status of life events experiences in Chinese students aged 16–24 years and analyze the combined effects of physical activity and life events on their depression and PTSD. Methods An online cross-sectional survey was conducted on physical activity levels, life events experiences, depression and PTSD of 1,552 Chinese students aged 16–24 using short version of International Physical Activity Questionnaire (IPAQ-S), adolescent self-rating life events checklist (ASLEC), PTSD Check List-Civilian Version (PCL-C) and Patient Health Questionnaire Depression Scale. Then, logistic regression equation and stratified analysis were used to explore the combined effects of physical activity and life events on depression and PTSD. Results Regression analysis showed that, except for female, <8 h of sleep, smoking, single parent/reorganized families and poor family economic status, experiencing medium-intensity and high-intensity life events were both risk factors for depression. Compared with those who experienced low-intensity life events, those who experienced medium- and high-intensity life events had a 27 and 131% increased risk of depression, respectively. In contrast, medium- and high-level physical activity could reduce the risk of depression by 49 and 53%, respectively. Similar results were obtained with PTSD as a dependent variable. Combined correlation analysis showed that, compared with those with high-level physical activity and low-intensity life events, those with low-level physical activity and high-intensity life events had a 209 and 121% increased risk of depression and PTSD, respectively. Stratified analysis showed that the threshold for life events induced depression and PTSD rose with the increase in the level of physical activity. Conclusion Lack of physical activity and experience of high-intensity life events are independent risk factors for depression and PTSD, and strengthening physical activity can compensate for the harm of depression and PTSD caused by life events to some extent.